Euphemistic names of a snake based on its habitat and behaviour - Smetona, Marius (Lietuvių kalba, 2014)
Scholarly works on snake euphemisms have not been numerous, yet it is worth mentioning a recent article “Euphemistic snake names” by B. Jasiūnaitė and M. Smetona (2013). This publication deals with euphemistic words that refer to a snake, the motivation of which is based on a snake’s appearance. The article “Euphemistic names of a snake based on its habitat and behaviour” may be considered as a further study on euphemistic snake names adding further knowledge to the above-mentioned publication. The present article relies on the definitions of euphemisms provided in the works by V. Želvis and J. Frazer and aims at classifying, analysing and describing 66 euphemistic snake names which appeared on the basis of the habitats snakes like to live in, their supposed or actual traits and behaviour. With respect to function, the majority of snake euphemisms are enigmatic (serving the functional purpose of disguise) and only a small part constitutes the class of complimentary euphemisms. Both enigmatic and complimentary euphemisms most often are suffixal derivatives. It is common that the motivating factors for such euphemisms to occur are physical reality related to snakes. In other words, once people have encountered a snake and got familiar with its environment, they have ascribed certain behavioural traits to it and noted in which areas it is usually known to occur. Euphemisms the base word of which refers to mystical beliefs (skraiduõlė and skraiduõlinė paskraiduõlinė) or euphemisms that are based on words the meaning of which presumably has nothing in common to snakes which are used in order to flatter them (e.g., čilbùtė, čiulbùtė ) are not common.